High-Sensitivity Mim Waveguide Sensor with Triple Fano Resonances for Multi-Parameter Detection of Plasma and Ammonium Chloride - Chen, D (WILEY, 2025)
This study proposes a highly sensitive metal-insulator-metal waveguide Nano-Refractive index sensor with triple Fano resonances for multi-parameter detection of plasma and ammonium chloride. Through coherent interference between discrete cavity modes and a broadband continuum, three distinct Fano resonances can be excited. The optimized sensor achieves a high refractive index sensitivity of up to 2219 nm/RIU. In practical testing, the sensor demonstrated a concentration sensitivity of 0.452 nm/(g/L) for ammonium chloride and 0.392 nm/(g/L) for plasma. This design supports simultaneous and time-shared detection of multiple analytes, offering a promising platform for real-time and efficient sensing in biomedical and industrial applications.